2022
DOI: 10.1088/1361-651x/ac5232
|View full text |Cite
|
Sign up to set email alerts
|

Pair structure, diffusion and pressure in liquid CuZr alloys from ab initio simulations: assessing the sensitivity to the energy cutoff

Abstract: An accurate determination of the liquid structure, dynamics and thermodynamics on the same footing from ab initio molecular dynamics requires particular attention in setting up the electronic structure calculation. Using two well established simulation codes implementing the density functional theory with modern projector augmented wave sets, extensive ab initio molecular dynamics runs have been performed on the CuZr liquid alloy, a prototype of glass-forming alloys. Simulation cells involving about 3000 elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…They are not shown in figure 2 as they are indistinguishable at the scale of the figure from the ones computed with the specialized potential. This confirms the general observation that the pair structure in liquid metals is not very sensitive to details of the EAM potential energy, in contrast with the pressure [26].…”
Section: Pure Rusupporting
confidence: 89%
See 4 more Smart Citations
“…They are not shown in figure 2 as they are indistinguishable at the scale of the figure from the ones computed with the specialized potential. This confirms the general observation that the pair structure in liquid metals is not very sensitive to details of the EAM potential energy, in contrast with the pressure [26].…”
Section: Pure Rusupporting
confidence: 89%
“…The EAM has been largely used to investigate copper based alloys-see for example [24,25] and references therein. In our recent study of the effect of the energy cutoff in CuZr binaries [26], we observed that EAM force fields with various forms of the pair terms may lead to a pair structure that agrees well with aiMD simulations. A good agreement with experiment was also found [27] when the FF was optimized using the Stillinger-Weber potential [28].…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations